Life preservation in Genesis and Exodus: an exegetical study of the Tēbâ of Noah and Moses - Spoelstra, Joshua Joel (Contributions to biblical exegesis and theology, 2020)
Tebâ' is found exclusively in Gen 6-9 and Exod 2:1-10 for the vessels of Noah and Moses, respectively. Suggestive of an inter-textual relationship, tebâ is exegetically investigated to identify its source language and meaning to thereby determine its biblical appropriation and theological signification. Once the Flood Narrative and Foundling Narrative are synchronically and diachronically analysed, Babylonian and Egyptian languages, literature, and lexemes are examined to determine the source of tebâ; also, a recension history of scriptural traditions and daughter translations of the Flood and Foundling Narratives is charted. Exod 15:1-21 is examined, further, to extend the narratival arch of Exod to match that of Gen 6-9, which includes synthetic cosmological and covenantal elements, and temple ideology. Theologically, therefore, the multivocality of tebâ intimates God?s enshrined protection of a person from threat of death unto renewed life; thus, tebâ is a terminus technicus for a life-preserving receptacle